Exploring Blended Learning Models Enhanced by Mobile Interactive Technology in Higher Education - Zhang, Ye (International Journal of Interactive Mobile Technologies (iJIM), 2024)
With the continuous advancement of information technology, mobile interactive technology has been increasingly applied in higher education, providing robust support for blended learning models. These models integrate the advantages of traditional classroom teaching and online learning, enhancing the flexibility and interactivity of the educational process. In recent years, research on mobile interactive technology and blended learning has expanded. However, most studies have primarily focused on the application of technological tools and platform construction, with limited exploration of specific interaction models and learning experiences. Furthermore, research on student learning objective identification and group stratification have been constrained, failing to effectively meet the needs of personalized learning. In response, this study explores the integration of interaction models and learning experiences within a mobile environment for university students in blended learning settings. Additionally, methods for identifying learning objectives and stratifying student groups based on mobile technology were investigated, aiming to provide theoretical and practical guidance for the implementation of blended learning in higher education.